Gut microbiome profile of Namalycastis sp. at Setiu wetland in Terengganu, Malaysia - SHUMPEI IEHATA; SITI RABAAH HAMZAH; SITI SYAZWANI AZMI; YUSOF SHUAIB IBRAHIM (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Iehata S, Hamzah SR, Azmi SS, Ibrahim YS. 2025. Gut microbiome profile of Namalycastis sp. at Setiu wetland in Terengganu, Malaysia. Biodiversitas 26: 358-367. Marine worm regulates the surrounding sediment microbial composition structure and diversity. While there are increasing reports on marine worm-related microbiome assemblage and their functional role in the ecosystem, more knowledge still needs to be reported on the gut microbiome associated with the Nypa worm (Namalycastis sp.). The present study conducted 16S rRNA gene amplicon sequencing to investigate the microbiome community of the Nypa worm gut as well as the environmental sample (rotten Nypa and surrounding water) and analyzed potential microbial functions using functional annotation of prokaryotic taxa (FAPROTAX). Principal coordinates analysis (PCoA) and upset plot results revealed the obvious relationship between microbiome compositions associated with Namalycastis sp. gut and their habitat (Nypa). Similarly, some genera, such as genus Demequina, were found to be in higher abundance in Namalycastis sp. gut and Nypa. This higher abundance could indicate a symbiotic relationship or a specific adaptation to the Nypa environment. Functional predictions based on FAPROTAX indicated that Nypa worms possess higher potentials for aromatic hydrocarbon degradation, aromatic compound degradation, aliphatic non-methane hydrocarbon degradation, and hydrocarbon degradation than environmental samples. The findings in this study suggested that the Nypa worm gut is a reservoir of several beneficial bacteria, such as Rhodococcus and Saccharimonadales, which create a unique microbial environment that facilitates the microbiological degradation of organic compounds. In addition, the genus Rhodococcus and candidatus Xiphinematobacter would become potential biomarkers to monitor the shifting environmental condition of mangroves.